Features of Producing Non-Autoclaved Aerated Concrete With Additives of Mineral and Technogenic Raw Materials - Marzhan A. Sadenova; Natalya A. Kulenova; Olga V. Rudenko; Darya K. Anop (Chemical Engineering Transactions)
This article discusses issues related to the study of the possibility of developing a technology for the production of non-autoclaved cellular concrete. The results of testing the mechanical strength and density of non-autoclaved cellular concrete samples synthesised by varying the nature and concentration range of the introduced modifier components are presented. It has been established that modification of the original non-autoclaved cellular concrete containing ash and slag materials of the Kazakhstan TPP by adding 3 to 10 % (by weight of cement) of natural clinoptilolite from the Taizhuzgen deposit in Kazakhstan and 0.075-0.03 % (by water) of fullerenol (C60) allows stabilising the properties of the developed non-autoclaved cellular concrete. The studies are promising and will continue to obtain cellular concrete with specified characteristics suitable for the construction of earthquake-resistant residential buildings.